EFFECT OF EMPLOYEES' INTERPERSONAL COMMUNICATION ABILITY ON ACHIEVEMENT MOTIVATION IN MAIN MANDIRI KSP RABA BRANCH BIMA CITY - Rizki Julianto Putra; Jaenab Jaenab (Jurnal Ilmu Manajemen Profitability, 2021)
This study aims to determine the effect of employee interpersonal communication skills on achievement motivation at KSP Mandiri Utama Raba branch, Kota Bima. This type of research is associative, the research instrument used is a Likert scale questionnaire. The population used in this study were 32 employees at KSP Mandiri Utama Raba Branch, Bima City. The sample in this study were all employees at KSP Mandiri Utama Raba Branch, Bima City as many as 32 employees. The sampling technique used was saturated sampling technique. Data analysis techniques used are validity test, reliability test, simple linear regression analysis, simple correlation, determination test and t test. The results showed that there was an influence between interpersonal communication on achievement motivation at KSP Mandiri Utama Raba Branch of Bima City with t value greater than t table (9.999 2.042) and the form of the effect was significant.